The Fight for Balkan Latinity (II). The Aromanians after World War - Motta, Giuseppe (Richtmann Publishing, 2012)
The article focuses on the Vlach question after the first World War, when the Balkan region was finally divided amongthe different national States and the Ottoman Empire collapsed. In this period the Aromanian communities had to find a newpolicy inside a new scenario and addressed towards different options represented by Albania, Italy and Romania. In a first timeVlachs also tried to create an autonomous principality of Pindus but this experience was short-lived and did not produce tangibleresults. On the contrary, during the interwar period the Vlachs consolidated their privileged relationship with Romania andestablished an influent group at Bucharest, where they partecipated to the internal political life even supporting the most radicalmovements such as Corneliu's Codreanu Iron Guard.